An evaluation of the performance of pile-driving formulas - Aleria, Felner C. (2002)
This study presents an evaluation of the performance of six (6) dynamic pile-driving formulas in the prediction of the ultimate pile capacities of forty-eight (48) prestressed, precast concrete piles driven into silty sands. The six pile-driving formulas studied are the Engineering News, Modified Engineering News, Hiley, Janbu, Schenk and Danish formulas Predicted capacities (Ru) are compared with measured capacities that were obtained using high-strain dynamic pile load tests and CAPWAP analysis (Rm), and correlated statistically using high-strain dynamic pile load tests and CAPWAP analysis (Rm), and correlated statistically using linear regression analysis. In addition, the tendency of the pile driving formulas to underestimate/overestimate the measured capacity was investigated based on log-normal distribution plots and values of the mean, standard deviation and coefficient of variation of the calculated (Ru/Rm) ratios. Finally ,the resutls of the statistical analyses were used to determine appropriate factors of safety for use with each pile-driving formula for the calculation of allowable pile capacities.